Типи текстової сегментації: лінгвокогнітивний аспект - Багумян, О. (Лексикографічний бюлетень, 2006)
In the article we have focused primarily on the ways of modern English texts segmentation in applied aspects. Having described briefly a variety of textual segmentation, we can differentiate the basic textual units and possible reference relations among them. Each coherence relation described below is associated with one or more constraints that must be met for it to hold.